ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERBANDINGAN TRIGONOMETRI PADA SEGITIGA SIKU-SIKU BERDASARKAN KRITERIA WATSON DI KELAS X SMA KATOLIK RANTEPAO - Hersiyati Palayukan (INSPIRAMATIKA, 2018)
The purpose of this research is 1) to know and identify the mistake of the most (dominant) student of grade X of Catholic Senior High School Rantepao in solving the comparative problem of trigonometry based on criterion of Watson's error, 2) to know the factors causing the student to make mistake in solving the problem comparative tales of trigonometry for each category of Watson's error. The research is descriptive qualitative research using Case Study method. The results of this study indicate the type of error that most students do when working on the problem of trigonometric comparison is the error category above other/ao with the percentage of 21.28%, then the next error is the error category appropriate data/id with percentage 19.1%, followed by error the response rate conflict / rlc category is 17.02%, then the wrong category/ip error and the undirect manipulation/um error with the same percentage, ie 12.8%, then the error type which also has the same percentage rate of 8.5 % is omitted data/od category error and omitted conclusion/oc category error. Factors for each type of error are presented in the discussion and conclusions.